AUDIT SISTEM INFORMASI MANAJEMEN SEKOLAH MENGGUNAKAN FRAMEWORK COBIT 4.1 (INTI Nusa Mandiri, 2024)
The School Management Information System (SIMS) has brought many benefits, even though it has been implemented, SMPIT Ajimutu Global Insani Bekasi faces several challenges and problems that require special attention, including limitations in IT Strategic Planning, Less Optimal IT Risk Management, Evaluation of Automation Solutions, Security Information Systems, IT Service Performance Measurement, IT Governance have not been fully implemented in their entirety. This article discusses the application of the COBIT 4.1 framework  in conducting SIMS audits at SMPIT Ajimutu Global Insani Bekasi. This research aims to assess the suitability of the information system with the school's strategic objectives, identify strengths and weaknesses in its management, and provide recommendations for improvement. The methodology used includes evaluation of the four main domains in COBIT 4.1: Planning and Organization (PO), Acquisition and Implementation (AI), Delivery and Support (DS), and Monitoring and Evaluation (ME). The audit results show that although SIMS has provided significant benefits, there are several areas that require improvement, such as IT strategic plan documentation, risk management, evaluation of automation solutions, information system security, IT service performance measurement, and IT governance. Based on these findings, recommendations for improvement are provided which include improving documentation and communication, developing formal processes for risk management, routine evaluation of automation solutions, improving security policies, establishing more comprehensive performance metrics, and strengthening IT governance.
Keywords: audit; COBIT 4.1; SIMS; SMPIT